2016
DOI: 10.1002/mbo3.415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pine wilt disease: roles of the pine endophytic bacteria and of the bacteria carried by the disease‐causing pinewood nematode

Abstract: Pine wilt disease (PWD) is one of the most destructive diseases in trees of the genus Pinus and is responsible for environmental and economic losses around the world. The only known causal agent of the disease is the pinewood nematode (PWN) Bursaphelenchus xylophilus. Despite that, bacteria belonging to several different genera have been found associated with PWN and their roles in the development of PWD have been suggested. Molecular methodologies and the new era of genomics have revealed different perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 145 publications
5
86
1
Order By: Relevance
“…This compound was previously described as being produced by nematode-associated bacteria causing wilting symptoms (Proença, Grass, & Morais, 2016). In the genomes of P. yamanorum (accession number LT629793) and P. extremaustralis strains (accession numbers FUYI00000000.1, LT629689 and AHIP00000000.1), we found genes coding for enzymes for the complete degradation of benzoate, a common intermediate in the anaerobic metabolism of toxic compounds, like phenols and other aromatic metabolites produced by the tree as a defence mechanism.…”
Section: Re Sults and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This compound was previously described as being produced by nematode-associated bacteria causing wilting symptoms (Proença, Grass, & Morais, 2016). In the genomes of P. yamanorum (accession number LT629793) and P. extremaustralis strains (accession numbers FUYI00000000.1, LT629689 and AHIP00000000.1), we found genes coding for enzymes for the complete degradation of benzoate, a common intermediate in the anaerobic metabolism of toxic compounds, like phenols and other aromatic metabolites produced by the tree as a defence mechanism.…”
Section: Re Sults and Discussionmentioning
confidence: 83%
“…The genomes of the four Pseudomonas strains had genes coding for the necessary enzymes for phenylacetate production. This compound was previously described as being produced by nematode-associated bacteria causing wilting symptoms (Proença, Grass, & Morais, 2016). This is the first study analysing the diversity of Pseudomonas associated with PWD.…”
Section: Re Sults and Discussionmentioning
confidence: 95%
“…It has been suggested that the bacteria, which produce a pine wilt toxin, along with the nematode are responsible for the rapid wilting of Japanese pine resulting from PWD (Oku et al ., ). These results and other findings indicate that bacteria associated with nematodes are essential for disease development (Zhao et al ., ; Proença et al ., ). On the other hand, pine endophytic bacteria were suggested to be part of the plant–nematode interaction by growth promotion or induction of resistance in pine trees (Nascimento et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These bacterial species have several roles in disease development, such as their ability to produce phytotoxins that damage plant cells (Han et al ., ). For pine endophytic bacteria, it has been suggested that such bacteria could have a role in induction of plant resistance, possibly by bacterial produced lipases (Nascimento et al ., ; Proença et al ., ). Moreover, analysis of the pine tree microbiome revealed several orthologues for traits related to plant growth promotion and plant defence factors such as chitinases (Alves et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The PGPR and biocontrol potentials have been proved for S. maltophilia in a number of studies (Elo, Maunuksela, Salkinoja-Salonen, Smolander, & Haahtela, 2000;Ruiu et al, 2017;Tashi-Oshnoei, Harighi, & Abdollahzadeh, 2017). The recent studies on pine wilt disease have shown that association of this bacterium with nematodes is the major causing factor of such diseases in pine wood (Arbuzova, Kulinich, Mazurin, & Zinov'eva, 2014;Cheng et al, 2013;He et al, 2016;Proença, Grass, & Morais, 2017). The recent studies on pine wilt disease have shown that association of this bacterium with nematodes is the major causing factor of such diseases in pine wood (Arbuzova, Kulinich, Mazurin, & Zinov'eva, 2014;Cheng et al, 2013;He et al, 2016;Proença, Grass, & Morais, 2017).…”
Section: Discussionmentioning
confidence: 99%